Penanaman Nilai Moderasi Beragama Melalui Pendidikan Dalam Keluarga Hindu Di Kota Mataram Provinsi Nusa Tenggara Barat - Gusti Ngurah Ketut Putera (Jurnal Penelitian Agama Hindu, 2022)
The view of one-sided truth claims that do not recognize the existence of other truths outside of themselves has resulted in disharmony in social relations resulting in rifts between components of society in a large group that vows to become one nation which is different but still has one common goal. The purpose of this study was to find the inculcation of the value of religious moderation through education in Hindu families in Mataram City, West Nusa Tenggara Province. This research is a qualitative study of the roles and strategies of Hindu families in the city of Mataram, West Nusa Tenggara, in instilling the value of moderation in children from an early age so that they can build relationships later in the heterogeneous society of Mataram City. From this study it was found that the role of the family as the main and first place of education was realized by Hindu family parents in the city of Mataram. The family also takes on the role of instilling the value of moderation as a provision and a form of adaptation for children to live in society later. The strategy applied is to use the story method and encourage heterogeneous association for children.